2017
DOI: 10.1097/mib.0000000000001075
|View full text |Cite
|
Sign up to set email alerts
|

Growth Improvement with Adalimumab Treatment in Children with Moderately to Severely Active Crohnʼs Disease

Abstract: ADA treatment resulted in growth rate normalization as early as week 26 in children with moderately to severely active Crohn's disease and growth impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…19 In the CD study, adalimumab sig-nificantly normalized the growth rate by week 26 (median height velocity z score, −0.34) and week 52 (0.21; both P < .001) in patients with baseline growth impairment (n = 73). 18 Linear growth remained stable over time in patients without baseline growth impairment (n = 27).…”
Section: Growthmentioning
confidence: 97%
See 1 more Smart Citation
“…19 In the CD study, adalimumab sig-nificantly normalized the growth rate by week 26 (median height velocity z score, −0.34) and week 52 (0.21; both P < .001) in patients with baseline growth impairment (n = 73). 18 Linear growth remained stable over time in patients without baseline growth impairment (n = 27).…”
Section: Growthmentioning
confidence: 97%
“…Patients with height velocity z score ≤-1.0 were considered to have growth delay at baseline. 18 Change from baseline in height velocity z score was evaluated in patients with and without growth delay at baseline.…”
Section: Safety Assessmentsmentioning
confidence: 99%
“…A study from Canada suggested that a positive effect on height velocity was observed only in pre-pubertal or pubertal patients, but was absent in patients with Tanner stage IV-V (43). The IMAgINE 1 study group has suggested that adalimumab also improved and normalized the growth rate of patients with CD at 26 and 52 weeks of treatment compared to baseline (44).…”
Section: Effect Of Ibd Treatment On Growth Of Patients With Pediatricmentioning
confidence: 99%
“…Population-based studies have shown that catch-up growth in pediatric IBD children occurs after initiation of anti-TNFα treatment (Crombé et al 2011;Church et al 2014). In a clinical trial of adalimumab in children with CD, this therapy significantly improved and normalized growth rate at weeks 26 and 52 in patients with baseline growth impairment (Walters et al 2017). Therefore, early anti-TNFα treatment is an example of a personalized treatment intervention for children with CD and linear growth failure.…”
Section: Bone Healthmentioning
confidence: 99%